Question
upstudy study bank question image url

10. Demonstrate and explain how to find the derivative of the following functions. Be sure to explicitly denote which derivative rules (scalar multiple, sum/difference, quotient, etc.) you are using in your work. \( \begin{array}{ll}\text { (c) } \\ h(w)=\sqrt[4]{w^{7}}+\frac{4}{w^{3}}\end{array} \)

Ask by Lynch Hill. in the United States
Feb 26,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The derivative of \( h(w) = \sqrt[4]{w^{7}} + \frac{4}{w^{3}} \) is \( h′(w) = \frac{7}{4}w^{\frac{3}{4}} - 12w^{-4} \).

Solution

We are given the function   h(w) = √[4]{w⁷} + 4/w³. Step 1. Rewrite the Function Using Exponents It’s easier to differentiate if we express the roots and reciprocals as exponents: • The fourth root of w⁷ can be written as w^(7/4), since √[4]{w⁷} = w^(7/4). • The term 4/w³ is equivalent to 4w^(–3). Thus, we have:   h(w) = w^(7/4) + 4w^(–3). Step 2. Differentiate Using the Power Rule and Sum Rule The rules we will use are:  • Sum Rule: The derivative of a sum is the sum of the derivatives.  • Power Rule: For any real number n, the derivative of wⁿ is n·w^(n–1).  • Constant Multiple Rule: The derivative of a constant times a function is the constant times the derivative of the function. Differentiate each term one at a time: A. Differentiate w^(7/4):  Using the Power Rule:   d/dw [w^(7/4)] = (7/4)·w^(7/4 – 1).  Compute the new exponent:   7/4 – 1 = (7/4 – 4/4) = 3/4.  Thus,   d/dw [w^(7/4)] = (7/4)·w^(3/4). B. Differentiate 4w^(–3):  Using the Constant Multiple Rule together with the Power Rule:   d/dw [4w^(–3)] = 4·d/dw [w^(–3)] = 4·(–3)w^(–3–1).  Compute the new exponent:   –3 – 1 = –4.  Thus,   d/dw [4w^(–3)] = –12w^(–4). Step 3. Combine the Results Now, apply the Sum Rule to add the derivatives of both terms:   h′(w) = (7/4)·w^(3/4) – 12w^(–4). This is the derivative of the function h(w). Summary of Derivative Rules Used: 1. Sum Rule: d/dw [f(w) + g(w)] = f′(w) + g′(w). 2. Power Rule: d/dw [wⁿ] = n·w^(n–1) (applied to both terms). 3. Constant Multiple Rule: d/dw [c·f(w)] = c·f′(w). Thus, the final answer is:   h′(w) = (7/4)w^(3/4) – 12w^(–4).

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Extra Insights

To find the derivative of \( h(w) = \sqrt[4]{w^{7}} + \frac{4}{w^{3}} \), we will use the sum rule and the power rule. 1. Rewrite \( \sqrt[4]{w^{7}} \) as \( w^{7/4} \) and \( \frac{4}{w^{3}} \) as \( 4w^{-3} \). 2. Now, differentiate: - For \( w^{7/4} \), use the power rule: \[ h'(w) = \frac{7}{4}w^{(7/4)-1} = \frac{7}{4}w^{3/4} \] - For \( 4w^{-3} \), again use the power rule: \[ h'(w) = 4 \cdot (-3)w^{-3-1} = -12w^{-4} \] So, combine these results using the sum rule: \[ h'(w) = \frac{7}{4}w^{3/4} - 12w^{-4} \] Voilà! The derivative of the function has been successfully derived while clearly denoting the rules applied.

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy